Polymorphisms affecting miRNA regulation: a new level of genetic variation affecting disorders and diseases of the human CNS. (July 2013) - Saba, Reuben; Booth, Stephanie A
The recognition of people and/or populations at a high risk for the development of various types of neurological disorders and diseases is not only key to improved screening programs and earlier detection, but it also provides hope for appropriate treatment and care. Genetic alterations that change gene-expression levels have long been investigated for association with the development of pathological neurological conditions. Gene regulation by miRNAs is a relatively new area of study, and published evidence suggests that alterations in this process may be associated with increased disease risk. Here, the authors review the current data for association between single nucleotide polymorphisms (SNPs) and miRNA-mediated gene regulation (miR-SNPs) in human neuropsychiatric and neurodegenerative diseases. Additionally, we present an approach to detect and identify functional miR-SNPs for the purpose of carrying out large-scale genetic association studies. The growing body of literature suggests that miR-SNPs are emerging as a powerful tool, both to study the pathobiology of diseases, as well as aiding in its diagnosis and prognosis.